2020
DOI: 10.3389/fpubh.2020.00477
|View full text |Cite
|
Sign up to set email alerts
|

Bibliometric Analysis on COVID-19: A Comparison of Research Between English and Chinese Studies

Abstract: Background: As an emerging infectious disease, COVID-19 has garnered great research interest. We aimed to explore the differences between English language and Chinese language Medical/Scientific journals publications, particularly aiming to explore the efficacy/contents of the literature published in English and Chinese in relation to the outcomes of management and characterization of COVID-19 during the early stage of COVID-19 pandemic. Methods: Publications on COVID-19 research were retrieved from both Engli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
63
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 105 publications
(90 citation statements)
references
References 43 publications
(49 reference statements)
2
63
0
9
Order By: Relevance
“…and there are still new cases of COVID-19 in China (18). The most urgent task for medical doctors or scientists is to control COVID-19, including the development of a safe and effective vaccine.…”
Section: Wwwbiosciencetrendscommentioning
confidence: 99%
See 1 more Smart Citation
“…and there are still new cases of COVID-19 in China (18). The most urgent task for medical doctors or scientists is to control COVID-19, including the development of a safe and effective vaccine.…”
Section: Wwwbiosciencetrendscommentioning
confidence: 99%
“…A large number of studies have applied bibliometric analyses to identify research trends in various fields (14). There are a few published studies about COVID-19 using bibliometric analysis to explore the activity and trends (18)(19)(20). However, no bibliometric study on recent scientific output and future research trends of COVID-19 vaccine was reported.…”
Section: Introductionmentioning
confidence: 99%
“…In relation to COVID-19, different bibliometric studies have been conducted at global level considering all fields of science (Kambhampati et al 2020;Lou et al 2020;Mao et al 2020;Mohadab et al 2020;Zyoud and Al-Jabi 2020). Other studies were at regional or country level (i.e., in Latin America and India) (Gallegos et al 2020;Raju and Patil 2020), in a specific filed of science (i.e., in the field of business and management) (Verma and Gustafsson 2020), comparison between English and Chinese studies (Fan et al 2020), or in a collection of a specific sources (i.e., nursing sources) (Oh and Kim 2020). The present study is the first of its kind that addressed COVID-19 research activities in the environmental sources.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the impending Chinese New Year, more than 5 million people traveled from Wuhan for either family reunions and/or holidays (5), contributing to the subsequent outbreak of COVID-19 in every province/region in China within a matter of weeks (6) that evolved into a pandemic within a matter of months (7). In response to the spread of the virus, a strict lockdown was implemented in late January 2020 in China in an attempt to stop person-to-person transmission, including the mandatory use of face masks in public, no public gatherings, and school and factory closures (8). It has been striking to observe that these measures were able to substantially reduce the number of COVID-19 cases to close to zero within a month, i.e., by February 2020 (9).…”
Section: Introductionmentioning
confidence: 99%